A Novel Approach for Detection of Fraud Using SOM - Barik, Swati Sucharita (International Journal of Computer Sciences and Engineering, 2025)
Fraud refers to abuse of organization’s system illegally. Fraud is the crime or offense of deliberately deceiving in order to damage them to obtain property or services unjustly. Fraud can be accomplished through the aid of forged objects. The scope of this paper is to investigate whether data mining techniques can be used for detecting fraud.